An empirical analysis of changes in credit rating properties: Timeliness, accuracy and volatility - Cheng, Mei; Neamtiu, Monica (Journal of Accounting and Economics, 2009)
In recent years, credit rating agencies have faced increased regulatory pressure and investor criticism for their ratings’ lack of timeliness. This study investigates whether and how rating agencies respond to such pressure and criticism. We find that the rating agencies not only improve rating timeliness, but also increase rating accuracy and reduce rating volatility. Our findings support the criticism that, in the past, rating agencies did not avail themselves of the best rating methodologies/efforts possible. When their market power is threatened by the possibility of increased regulatory intervention and/or reputation concerns, rating agencies respond by improving their credit analysis.